"What is, Becomes What is Right" A Conceptual Framework of Newcomer Legitimacy for Online Discussion Communities. - Savage, Timothy; Gallagher, Silvia (My University, 2015)
Online community newcomers can face challenges in community participation, acceptance and fostering member relationships. Consequently, a crucial behavioral strategy for community acceptance identified by previous research is legitimacy. However, current conceptions lack classification and structure, and have a narrow focus. A broader scope for investigating legitimacy is needed for improved theoretical and practical application. This research expands on newcomer legitimacy by classifying newcomer behavior in 4 parenting and cycling discussion communities using directed content analysis. The analysis developed a newcomer legitimacy conceptual framework with categories including geographical, contextual, cultural, testimonial, lurking and external legitimacy. This research offers a valuable contribution by classifying existing theory, developing new theory, and providing a conceptual framework to guide future studies of newcomer behavior.
PUBLISHED
Keywords: Online community; Newcomers; Legitimacy; Conceptual framework; Directed content analysis; Social role; Technology in Education; VIRTUAL COMMUNITY